Lewis Eller Asher autograph collection - Asher, Louis Eller, 1877-1948.
Engraved portraits and autograph letters and documents of all U.S. presidents from George Washington to William Howard Taft (except John Adams) and all vice presidents from Aaron Burr to Charles W. Fairbanks; and other autograph documents. Correspondents of the presidents include Richard K. Call, Isaac Shelby, and Littleton W. Tazewell.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Autograph collector.
Keywords: Adams, John Quincy, -- 1767-1848 -- Autographs; Arthur, Chester Alan, -- 1829-1886 -- Autographs; Breckinridge, John C. -- 1821-1875 -- Autographs; Buchanan, James, -- 1791-1868 -- Autographs; Burr, Aaron, -- 1756-1836 -- Autographs; Calhoun, John C. -- 1782-1850 -- Autographs; Call, R. K. -- 1791-1862 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Autographs; Clinton, George, -- 1739-1812 -- Autographs; Colfax, Schuyler, -- 1823-1885 -- Autographs; Dallas, George Mifflin, -- 1792-1864 -- Autographs; Fairbanks, Charles W. -- 1852-1918 -- Autographs; Fillmore, Millard, -- 1800-1874 -- Autographs; Garfield, James A. -- 1831-1881 -- Autographs; Gerry, Elbridge, -- 1744-1814 -- Autographs; Grant, Ulysses S. -- 1822-1885 -- Autographs; Hamlin, Hannibal, -- 1809-1891 -- Autographs; Harrison, Benjamin, -- 1833-1901 -- Autographs; Harrison, William Henry, -- 1773-1841 -- Autographs; Hayes, Rutherford Birchard, -- 1822-1893 -- Autographs; Hendricks, Thomas A. -- 1819-1885 -- Autographs; Hobart, Garret A. -- 1844-1899 -- Autographs; Jackson, Andrew, -- 1767-1845 -- Autographs; Jefferson, Thomas, -- 1743-1826 -- Autographs; Johnson, Andrew, -- 1808-1875 -- Autographs; Johnson, Richard M. -- 1781-1850 -- Autographs; King, William R. -- 1786-1853 -- Autographs; Lincoln, Abraham, -- 1809-1865 -- Autographs; Madison, James, -- 1751-1836 -- Autographs; McKinley, William, -- 1843-1901 -- Authographs; Monroe, James, -- 1758-1831 -- Autographs; Morton, Levi P. -- 1824-1920 -- Autographs; Pierce, Franklin, -- 1804-1869 -- Autographs; Polk, James K. -- 1795-1849 -- Autographs; Roosevelt, Theodore, -- 1858-1919 -- Autographs; Shelby, Isaac, -- 1750-1826 -- Correspondence; Stevenson, Adlai E. -- 1835-1914 -- Autographs; Taft, William H. -- 1857-1930 -- Autographs; Taylor, Zachary, -- 1784-1850 -- Autographs; Tazewell, Littleton Waller, -- 1774-1860 -- Correspondence; Tompkins, Daniel D., -- 1774-1825 -- Autographs; Tyler, John, -- 1790-1862 -- Autographs; Van Buren, Martin, -- 1782-1862 -- Autographs; Washington, George, -- 1732-1799 -- Autographs; Wheeler, William A. -- 1819-1887 -- Autographs; Wilson, Henry, -- 1812-1875 -- Autographs; Presidents -- United States -- Autographs; Vice presidents -- United States -- Autographs; Collectors, Autograph